H1N1 influenza A virus-associated acute lung injury: response to combination oseltamivir and prolonged corticosteroid treatment - Quispe-Laime, Adolfo Maximo (Intensive Care Med, 2009)
PURPOSE: During the 2009 H1N1 influenza A virus pandemic, a minority of patients developed rapidly progressive pneumonia leading to acute lung injury (ALI)—acute respiratory distress syndrome (ARDS). A recent meta-analysis provides support for prolonged corticosteroid treatment in ALI-ARDS. We prospectively evaluated the response to oseltamivir and prolonged corticosteroid treatment in patients with ALI-ARDS and suspected H1N1 influenza. METHODS: From June 24 through 12 July 2009, 13 patients with suspected H1N1 pneumonia and ALI-ARDS were admitted to the intensive care unit (ICU) of a tertiary care hospital. H1N1 influenza was confirmed with real-time reverse transcriptase-polymerase chain reaction assay in eight patients. Oseltamivir and corticosteroid treatment were initiated concomitantly at ICU admission; those with severe ARDS received methylprednisolone (1 mg/kg/day), and others received hydrocortisone (300 mg/day) for a duration of 21 ± 6 days. RESULTS: Patients with and without confirmed H1N1 influenza had similar disease severity at presentation and a comparable response to treatment. By day 7 of treatment, patients experienced a significant improvement in lung injury and multiple organ dysfunction scores (P < 0.001). Twelve patients (92%) improved lung function, were extubated, and discharged alive from the ICU. Hospital length of stay and mortality were 18.7 ± 9.6 days and 15%, respectively. Survivors were discharged home without oxygen supplementation. CONCLUSIONS: In ARDS patients, with and without confirmed H1N1 influenza, prolonged low-to-moderate dose corticosteroid treatment was well tolerated and associated with significant improvement in lung injury and multiple organ dysfunction scores and a low hospital mortality. These findings provide the rationale for developing a randomized trial.